2016
DOI: 10.1016/j.canep.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Overall and recurrence-free survival among black and white bladder cancer patients in an equal-access health system

Abstract: Background While the incidence of bladder cancer is twice as high among whites than among blacks, mortality is higher among blacks than whites. Unequal access to medical care may be an important factor. Insufficient access to care could delay cancer detection and treatment, which can result in worse survival. The purpose of this study was to evaluate whether survival differed between black and white bladder cancer patients in the Department of Defense (DoD), which provides universal healthcare to all beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…DeDeugd et al found that African-Americans initially present with more aggressive BLCA, however, African-Americans actually have an improved overall survival compared with Caucasians [23]. However, Schinkel et al reported that white and black patients with BLCA were not significantly different in overall and recurrence-free survival regardless of muscle invasion [24]. In the present study, when the patients with BLCA were stratified by race, the results showed that for the Caucasians, they can be divided into either a high-risk group with shorter survival or a low-risk group with longer survival according to the eight-lncRNA signature.…”
Section: Discussionmentioning
confidence: 99%
“…DeDeugd et al found that African-Americans initially present with more aggressive BLCA, however, African-Americans actually have an improved overall survival compared with Caucasians [23]. However, Schinkel et al reported that white and black patients with BLCA were not significantly different in overall and recurrence-free survival regardless of muscle invasion [24]. In the present study, when the patients with BLCA were stratified by race, the results showed that for the Caucasians, they can be divided into either a high-risk group with shorter survival or a low-risk group with longer survival according to the eight-lncRNA signature.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Furthermore, bladder cancer presents a high recurrence rate and mortality rate because of the absence of typical symptoms at the early stage. 6,7 No reliable biomarkers are helpful for clinical therapy and survival estimation. [8][9][10] Therefore, identifying effective biomarkers for early diagnosis and prognosis assessment is needed for the clinical therapy of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, these studies have suggested that access to care is a major contributor to disparities: For example, using a (fully insured) Medicare population, Schmid et al 8 found disparities in prostate cancer outcomes, as did Cullen et al 9 using a Veterans Affairs population. Similarly, Schinkel et al 22 found that patients with bladder cancer within a US Department of Defense cohort experienced fewer disparities in overall and recurrence-free survival.…”
Section: Discussionmentioning
confidence: 89%
“…19,20 There are also some ecological data indicating that racial and ethnic differences may be lessened in equal-access health systems. 21,22 In this setting, we designed a study to compare the overall survival of black and white patients diagnosed with localized muscle-invasive bladder cancer and to assess the relative contributions of tumor characteristics, treatment type, and access-related factors (insurance, income, education, and distance to a hospital) to the excess risk of death among blacks. We hypothesized that black individuals with bladder cancer would have worse overall survival than white patients and that access-related variables (insurance, education, income, and distance to a hospital) would explain the majority of the excess mortality in black men and women with bladder cancer.…”
Section: Introductionmentioning
confidence: 99%